Science encyclopedia : atom smashing, food chemistry, animals, space, and more! (Washington, D.C. : National Geographic, 2016)
Offers an illustrated encyclopedia of general science, with informative and fun facts on a broad array of scientific topics.
Part 1: Physical science: Matter -- Forces and machines -- Energy -- Electronics -- Part 2: Life science: The universe -- Life on Earth -- The human body -- Planet Earth.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Age 8-12.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Science -- Encyclopedias, Juvenile; Science -- Encyclopedias, Juvenile; JUVENILE NONFICTION -- Reference -- Encyclopedias; JUVENILE NONFICTION -- Science & Nature; JUVENILE NONFICTION -- Technology; Science; Electronic books- OSLIS; Juvenile works; Encyclopedias; Encyclopedias; Juvenile works; Encyclopedias; Electronic books